Immunochemical study of human apolipoprotein E: Development of LDL-receptor mimetic monoclonal antibodies, using recombinant DNA approaches. - Raffai, Robert Leslie. (University of Ottawa (Canada), 1998)
Apolipoprotein (apo)E is a 299 amino acid polypeptide that plays an important role in plasma lipoprotein metabolism. A major physiological function of apoE resides in its ability to be specifically recognized by cellular low-density-lipoprotein receptors (LDLr). A common apoE isoform is defective in its binding to the LDLr and its inheritance can lead to hyperlipidemia. In addition to apoE genetic polymorphism, apoE interaction with the LDLr also depends on apoE conformation. While lipid-free apoE cannot interact with the LDLr, upon binding to lipid, apoE undergoes a conformational change that renders it receptor-competent. Within plasma lipoproteins, apoE is conformationally heterogeneous, with only a subpopulation of apoE molecules having the ability to mediate binding to the LDLr. The goal of my thesis was to investigate the structural modalities that determine the ability of LDL to bind to the LDLr. To this end, I have made use of novel recombinant antibody methodologies, in order to probe the structural basis of the apoE-LDLr interaction. I demonstrate that a monoclonal antibody that is specific for the LDLr binding site on apoE resembles the LDLr in terms of fine specificity and primary structure. Furthermore, by in vitro mutagenesis, I was able to generate a series of variants that differ from the parental antibody in both affinity and apoE isoform specificity. Of particular interest, one variant acquired the ability to recognize apolipoprotein B100, the other ligand of the LDLr. I argue that this variant is an antibody mimetic of the LDLr This panel of anti-apoE recombinant antibodies will be useful reagents for determining the mechanisms involved in the interaction of the LDLr and its ligands. In more general terms, it offers a unique model for studying the molecular recognition processes that occur between protein macromolecules.
Keywords: Biology, Molecular.